Universal periodic review: the role of civil society organisations in Malaysia / Sarune Beh, Nurhidayah Abdullah and Makmor Tumin - Beh, Sarune; Abdullah, Nurhidayah; Tumin, Makmor (Universiti Teknologi MARA, 2020)
In Malaysia, the participation of citizens in public-policy process is still deemed limited under the semiauthoritarian state. The Universal Periodic Review (UPR) provides a great avenue to illustrate the role of Civil Society Organisations (CSOs) in public policy-making as it brings into focus highly debatable human rights issues in the international arena. This paper examines the influence of CSOs in the state's decision making in the UPR process, and identifies the role of CSOs in the Malaysian UPR by investigating the interaction between the state and CSOs from the perspectives of political culture, organisational imperatives and functional coincidence, and behavioural and attitudinal approaches. A qualitative approach was applied through the use of in-depth interviews and an analysis of secondary data. Our findings show that CSOs' participated actively in the UPR process but this participation remained limited in a procedural democratic setting although the state has become more open to CSOs. This has resulted in CSO influence being more targeted towards conservative rather than controversial issues in the UPR. This paper aspires to contribute to the existing body of knowledge on democracy, focusing on its substantive practices in public decision-making processes within government institutions with regards to human rights policies.